Handbook of monetary economics - Arrow, Kenneth J (Ed.); Intriligator, Michael D (Ed.) (Amsterdam Elsevier Science, 1990)
The handbook of monetary economics is in two volumes.The First volumes contents-Transacttions role of money,Money in dynamics systems,Money demand and pricing,non money assets and the volumes two contents-Money inflation and welfare,Monetary ploicy etc.
Keywords: MONEY; MONETARY POLICY